Critique, Estrangement and Speculative Envisioning: Pedagogical Thinking and Otherwise Educational Worlds - Delgado Vintimilla, Cristina (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2023)
In this paper I draw on my work as a pedagogista to discuss the pedagogical promise of critique, estrangement, and what I call speculative envisioning. I argue that these concepts are themselves modes of engagement, practice, and thinking that are pedagogical and that they can help educators engage with the nondeterministic work of creating conditions for otherwise educational worlds. To do so I reassert critique’s promise by tracing the ways Michel Foucault and Judith Butler ask us to engage with it and consider what it might offer to education and, more specifically, to early childhood education. I then introduce estrangement as a pedagogical disposition towards otherwise educational worlds and as a means by which to consider speculative envisioning. I propose speculative envisioning as a mode of pedagogical thought that works as a necessary supplement to the renewal value of critique and how this constitutes a pedagogical and ethical move toward otherwise educational worlds.